Pengaruh Bimbingan Belajar Online “Ruangguru” Terhadap Hasil Belajar Siswa di SMA Negeri 5 Bukittnggi - Desma Wati; Deswalantri Deswalantri; Wedra Aprison; Hidayani Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study was motivated by the existence of online tutoring users ruangguru at SMA Negeri 5 Bukittinggi and aims to determine how much influence online tutoring (Ruangguru) has on the learning outcomes of students at SMA Negeri 5 Bukittinggi. This study uses a quantitative research method with a simple regression approach. The sampling technique uses purposive sampling where the sampling is based on certain considerations, the sample of this study was students in grades 1, 2, and 3 at SMA N 5 Bukittinggi totaling 65 people. Data were obtained through a questionnaire using a Likert scale that had been tested for validity. Data validity techniques use validity and reliability tests. Statistical testers with assumption test analysis (normality and linearity), linear regression analysis, hypothesis testing (F test and R2 test). Based on the analysis and data from the research results processed using the SPSS 22.0 computer program, it shows that partially it can be seen that the Variable X Ruangguru Online Learning Guidance on student learning outcomes has a constant of 19.993 and a coefficient value of 0.323 has a significance of 0.200> 0.05. It can be concluded that there is an influence of Ruangguru Online Learning Guidance on Student Learning Outcomes. Based on the Simultaneous test, the influence of Ruangguru Online Learning Guidance on Learning Outcomes is that f count 75.083> f table 2.90 and has a significant figure of 0.000 <0.05. This means that there is a Positive influence between Ruangguru Online Learning Guidance on Student Learning Outcomes at SMA N 5 Bukittinggi. With a determination coefficient value obtained of 0.544, this means that there is an influence of 29.59%, while the rest is influenced by other variables that are not studied.